2012
DOI: 10.1371/journal.pone.0050711
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Activation of Classic PKC and Estrogen Receptor α Is Involved in Estradiol 17ß-D-Glucuronide-Induced Cholestasis

Abstract: Estradiol 17ß-d-glucuronide (E17G) induces acute cholestasis in rat with endocytic internalization of the canalicular transporters bile salt export pump (Abcb11) and multidrug resistance-associated protein 2 (Abcc2). Classical protein kinase C (cPKC) and PI3K pathways play complementary roles in E17G cholestasis. Since non-conjugated estradiol is capable of activating these pathways via estrogen receptor alpha (ERα), we assessed the participation of this receptor in the cholestatic manifestations of estradiol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 47 publications
(65 reference statements)
1
37
0
Order By: Relevance
“…Our group has recently demonstrated that GPR30, a GPCR, and ERα accounts in part for the acute cholestasis caused by E17G Barosso et al 2012), event that correlates well with its ability to induce endocytic internalization of the canalicular transporters such as Abcc2 (Mottino et al 2003(Mottino et al , 2005. The actions of GPR30 and ERα in E17G-induced cholestasis constitute two independent pathways.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our group has recently demonstrated that GPR30, a GPCR, and ERα accounts in part for the acute cholestasis caused by E17G Barosso et al 2012), event that correlates well with its ability to induce endocytic internalization of the canalicular transporters such as Abcc2 (Mottino et al 2003(Mottino et al , 2005. The actions of GPR30 and ERα in E17G-induced cholestasis constitute two independent pathways.…”
Section: Discussionmentioning
confidence: 90%
“…Based on the IC50 value, the concentration of E17G used for transport studies was 100 µM. This value is the estimated concentration at which hepatocytes are exposed in perfused rat livers (3 µmol per liver administered during a minute in a perfusing flow of 30 mL/ min, Barosso et al 2012).…”
Section: Egfr Participates Of E17g-induced Impairment Of Canalicular mentioning
confidence: 99%
“…Furthermore, E 2 17G activates the estrogen receptor α (Erα) in isolated perfused rat liver 101. This might explain why chemical inhibition or knock‐down of ERα partially prevented decreased Bsep/Mrp2 activity and reduced transporter internalization 101. This finding is substantiated further by the observation that Erα(−/−) mice are resistant to ethinylestradiol‐induced hepatotoxicity 102.…”
Section: Mechanisms Of Drug‐induced Cholestasismentioning
confidence: 96%
“…E 2 17G activates classical, Ca 2+ ‐dependent protein kinase C and phosphoinositol 3‐kinase signaling pathways, which are cooperatively involved in internalization and intracellular retention of Bsep/Mrp2 99,100. Furthermore, E 2 17G activates the estrogen receptor α (Erα) in isolated perfused rat liver 101. This might explain why chemical inhibition or knock‐down of ERα partially prevented decreased Bsep/Mrp2 activity and reduced transporter internalization 101.…”
Section: Mechanisms Of Drug‐induced Cholestasismentioning
confidence: 99%
See 1 more Smart Citation